SISTIM KOMUNIKASI DALAM GAYA KEPEMIMPINAN UNTUK MENDAPATKAN KEPUASAN KERJA DOSEN - Dewi, Yuni Retna (Universitas Prof. Dr. Moestopo (Beragama), 2014)
This study is intended to show the impacts of management behavior and organization climate that are related to the job statisfaction on lecturers from the Faculty Communication Sciene, the University Of Prof. DR. Moestopo (Beragama)-FIKOM UPDM (B).The Research was carrying out by surveyâs method and it was done by simplerandom sampling technique with the respondents are about 75 lecturers from the faculty, as well as it was using questionnaire. The results of this study are as follows:Significant positive correlation between management behavior and lecturerâs Job Satisfaction. Equation regression is Y = 30,109 + 0,373 X1, with person product moment is about 0,522 or 22,72% of X1.Significant positive correlation between organization climate and lecturerâs Job Satisfaction. From the equation regression: Y = 22,342 + 0,502 X2, and Finally There was significant positive correlation between a combination of management behavior and organization climate that is related to job satisfaction of lecturer. The equation regression result is Y = 18,388 + 0,264 X1 + 0,329 X2.the determination coefficient is 0,597, while the contribution of management behavior and organization climate to the lecturerâs job satisfaction is about 35,4 5